Method for manufacturing electrode, electrode, and battery

By placing the first electrode layer and the second electrode layer coated with different resins in the lithium-ion secondary battery, the problem of high interface resistance between the electrode layer and the current collector is solved, and an electrode with excellent electron conductivity is achieved, thereby improving the Battery performance.

CN119480916APending Publication Date: 2025-02-18TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410561839.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-09
Filing Date
2024-05-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the conventional lithium-ion secondary battery, the interface resistance between the electrode layer and the current collector is high, and there is room for improvement in electron conductivity.

Method used

By placing the first electrode layer and the second electrode layer on the current collector, the first electrode layer is made by electrostatic film formation, wet film formation or calendering film formation, and the second electrode layer is made by calendering film formation. In the case where the first electrode layer is made of a calendered film, the surface of the active material particles is coated with a resin different from that of polytetrafluoroethylene (PTFE).

Benefits of technology

The interface resistance at the interface between the electrode and the current collector is reduced, and the electrode with excellent electron conductivity is achieved, which improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The method for manufacturing an electrode includes a step of fabricating a first electrode layer disposed on a current collector, and a step of fabricating a second electrode layer disposed on the first electrode layer. The first electrode layer is manufactured by electrostatic film formation, wet film formation, or calendering film formation. And the second electrode layer is manufactured by calendaring to form a film. In the case where the first electrode layer is produced by rolling film formation, at least a portion of the surface of the active material particles used in the rolling film formation is coated with a resin different from polytetrafluoroethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing an electrode, an electrode, and a battery. Background Art

[0002] In batteries such as lithium ion secondary batteries, electrodes are used in which active material particles are fixed on the surface of a current collector such as a metal foil with a binder. As methods for manufacturing electrodes, known methods include a method of applying a composition prepared by mixing active material particles, a binder and a solvent to the surface of a current collector (also called a wet method), and a method of fixing active material particles to a current collector using a binder without using a solvent (also called a dry method).

[0003] As a method for manufacturing an electrode based on a dry method, a method of using a resin having the property of being fibrillated (fibrillated) when a shear force is applied as a binder is proposed. For example, Japanese Patent Publication No. 2022-3694 describes the following method: PTFE in a mixture containing active material particles and polytetrafluoroethylene (PTFE) is fibrillated to make an electrode film, and then the electrode film is integrated with a collector to manufacture an electrode. Summary of the invention

[0004] Regarding the electrode obtained by the method described in Japanese Patent Application Laid-Open No. 2022-3694, the interface resistance at the interface between the electrode layer and the current collector is high, and there is room for improvement in electron conductivity. An object of one embodiment of the present disclosure is to provide a method for producing an electrode having excellent electron conductivity, an electrode having excellent electron conductivity, and a battery including an electrode having excellent electron conductivity.

[0005] Means for solving the above-mentioned problems include the following embodiments. <1> A method for manufacturing an electrode, comprising: a step of preparing a first electrode layer disposed on the current collector; and A step of manufacturing a second electrode layer disposed on the first electrode layer. The first electrode layer is produced by electrostatic film forming, wet film forming, or calendering film forming. The second electrode layer is produced by calendering film forming. When the first electrode layer is produced by calendaring film formation, at least a part of the surface of the active material particles used in the calendaring film formation is coated with a resin different from polytetrafluoroethylene. <2> according to <1> The method for producing an electrode as described above, wherein: The calendering film formation includes fiberizing polytetrafluoroethylene in a mixture containing active material particles and polytetrafluoroethylene. <3> according to <1> The method for producing an electrode as described above, wherein: The resin other than polytetrafluoroethylene is polyvinylidene fluoride. <4> An electrode, The invention comprises a current collector, a first electrode layer arranged on the current collector, and a second electrode layer arranged on the first electrode layer. The first electrode layer comprises active material particles and a resin having a polytetrafluoroethylene ratio of 0 mass % or more and less than 5 mass %, or comprises active material particles at least a portion of the surface of which is coated with a resin different from PTFE, and fibrous PTFE, The second electrode layer contains active material particles and fibrous PTFE. <5> A battery, It has <4> Recorded electrodes.

[0006] According to one embodiment of the present disclosure, there are provided a method for producing an electrode having excellent electron conductivity, an electrode having excellent electron conductivity, and a battery including the electrode having excellent electron conductivity. DETAILED DESCRIPTION

[0007] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the minimum value and the maximum value, respectively. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment. In the present disclosure, the term "process" refers not only to an independent process but also to a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved. In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment. In the present disclosure, when there are plural kinds of substances corresponding to each component, the amount of each component means the total amount of the plural kinds of substances unless otherwise specified. Electrode manufacturing method

[0008] The method for manufacturing an electrode disclosed herein comprises: a step of preparing a first electrode layer disposed on the current collector; and A step of manufacturing a second electrode layer disposed on the first electrode layer. The first electrode layer is produced by electrostatic film forming, wet film forming, or calendering film forming. The second electrode layer is produced by calendering film forming. When the first electrode layer is produced by calendaring film formation, at least a part of the surface of the active material particles used in the calendaring film formation is coated with a resin different from polytetrafluoroethylene.

[0009] The method for manufacturing an electrode disclosed herein includes: a step of manufacturing a first electrode layer disposed on a current collector, and a step of manufacturing a second electrode layer disposed on the first electrode layer. That is, the electrode manufactured by the method disclosed herein has a structure in which a current collector, a first electrode, and a second electrode are disposed in this order.

[0010] As shown in the embodiments described later, if the electrode layer configured on the collector is made by rolling film forming, the interface resistance at the interface between the electrode layer and the collector has a tendency to increase. As its reason, it is believed that the PTFE included as a binder in the electrode layer made by rolling film forming is low in bonding force for the collector. The electrode manufactured by the method disclosed herein is provided with a first electrode between the current collector and the second electrode layer formed by rolling film forming. The first electrode layer is made by electrostatic film forming, wet film forming, or rolling film forming, and at least a portion of the surface of the active material particles used in the rolling film forming is coated with a resin different from PTFE. Thus, the first electrode layer exhibits sufficient adhesion to the current collector. As a result, the interface resistance at the interface between the electrode and the current collector can be reduced, and good electronic conductivity can be achieved.

[0011] Hereinafter, the step of manufacturing the first electrode layer is also referred to as “step 1”, and the step of manufacturing the second electrode layer is also referred to as “step 2”. Process 1

[0012] In step 1, a first electrode is prepared and arranged on the current collector. The method for preparing the first electrode is electrostatic film forming, wet film forming, or calendaring film forming. When the method for preparing the first electrode is calendaring film forming, at least a part of the surface of the active material particles used in the calendaring film forming is coated with a resin different from PTFE.

[0013] In the present disclosure, “electrostatic film formation” means a method of forming an electrode layer by causing a material of the electrode layer to electrostatically adhere to a current collector. In the present disclosure, “wet film formation” means a method of forming an electrode layer by applying a composition obtained by adding a solvent to a material for an electrode layer to a current collector. In the present disclosure, "calendering film forming" means a method of calendering the material of the electrode layer containing PTFE to fibrillate the PTFE and make a sheet-like formed body. The electrode layer made by calendering film forming is not formed on the collector, but is made as an independent film. The calendering process can be carried out using a roller press etc.

[0014] Electrostatic film forming and calendering film forming in the above methods are classified as dry methods that do not use solvents. Therefore, when the first electrode layer is prepared by electrostatic film forming or calendering film forming, it is advantageous in terms of reducing the manufacturing cost of the electrode and reducing the impact on the environment and organisms.

[0015] The material used for preparing the first electrode includes, for example, active material particles and a binder, and may further include a conductive material as necessary. The type of active material particles is not particularly limited and can be selected from materials generally used in the production of electrodes. The active material particles may be positive electrode active material particles or negative electrode active material particles.

[0016] As the positive electrode active material, lithium transition metal composite oxides can be cited. As transition metals, Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. can be cited. Among them, preferably comprising at least one lithium transition metal composite oxide selected from Ni, Co and Mn, more preferably comprising Ni, Co and Mn lithium transition metal composite oxide (NCM, nickel cobalt manganese oxide). As lithium transition metal composite oxides, specifically, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and composite oxides thereof (LiCo x Ni y Mn z O2, x+y+z=1), a composite oxide containing an additional element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel lithium manganese oxide (LiMn2O4), olivine LiMPO4 (M: Co, Ni, Mn, Fe), etc. The positive electrode active material used in the preparation of the electrode layer may be a single type or two or more types. The volume average particle size of the positive electrode active material particles is not particularly limited, and can be selected from the range of 5 μm to 30 μm, for example.

[0017] Specific examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and silicon. The negative electrode active material used in the preparation of the electrode layer may be a single type or two or more types. The volume average particle size of the negative electrode active material particles is not particularly limited, and can be selected from the range of 5 μm to 30 μm, for example.

[0018] In the present disclosure, the volume average particle size of particles is a value (D50) at which the accumulation from the smaller diameter side becomes 50% in the volume-based particle size distribution measured by a laser diffraction scattering method.

[0019] The type of the binder is not particularly limited, and can be selected from materials generally used in the production of electrodes. Examples of binders used in the case of forming the first electrode layer by electrostatic film formation or wet film formation include polyvinylidene fluoride, polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylates, polymethacrylates, and the like. The binder used in the preparation of the first electrode layer may be one kind alone or two or more kinds. From the viewpoints of adhesive strength, affinity with PTFE included in the second electrode layer, electrolyte resistance, etc., polyvinylidene fluoride (PVdF) is preferred as the binder. From the viewpoint of adhesion to the current collector, it is preferred that the binder does not contain PTFE or the content of PTFE is less than 5% by mass.

[0020] As a binder in the case of producing the first electrode layer by calendering, PTFE can be cited. PTFE can be fibrous by calendering, and the active material particles can be bonded to form a sheet-like molded body. PTFE can be in particle form. When the first electrode layer is produced by calendaring film formation, the binder may be PTFE alone or a mixture of PTFE and a resin other than PTFE. When the binder in the case of producing the first electrode layer by calendering is a mixture of PTFE and a resin different from PTFE, the content of the resin different from PTFE in the mixture may be less than 20 parts by mass, less than 10 parts by mass, or less than 5% by mass relative to 100 parts by mass of PTFE.

[0021] The type of the conductive material is not particularly limited, and can be selected from materials generally used in the production of electrodes. Specific examples of the conductive material include carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes, and graphite. The conductive material used in the production of the electrode may be a single type or two or more types.

[0022] Among the materials for the first electrode layer, the amount of the binder relative to 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 to 10 parts by mass or 1 to 5 parts by mass. Among the materials for the first electrode layer, the amount of the conductive material relative to 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 to 10 parts by mass or 1 to 5 parts by mass.

[0023] When the material of the first electrode layer includes active material particles and a conductive material, a composite treatment may be performed to fix the conductive material to the surface of the active material particles. The method for performing the composite treatment is not particularly limited, and the composite treatment can be performed by a known method. For example, there is a method of applying a shear force to a mixture of active material particles and a conductive material. The composite treatment can be carried out in a state where the mixture of active material particles and conductive material contains a binder, or in a state where the mixture of active material particles and conductive material does not contain a binder. From the perspective of suppressing the separation of active material particles and conductive material, the composite treatment is preferably carried out in a state where the mixture of active material particles and conductive material contains a binder.

[0024] When the first electrode layer is produced by calendering, at least a portion of the surface of the active material particles used in the calendering is coated with a resin different from PTFE. The type of resin coating the surface of the active material particles is not particularly limited and can be selected from known materials. For example, it can also be selected from the above-mentioned binders. From the viewpoints of adhesive strength, affinity with PTFE contained in the first electrode layer, resistance to electrolyte, and the like, the resin that covers the surface of the active material particles is preferably polyvinylidene fluoride (PVdF). The method of coating the surface of the active material particles with a resin is not particularly limited and can be implemented by a known method. For example, the surface of the active material particles can be coated with a binder (i.e., a resin) used to fix the conductive material to the surface of the active material particles by the above-mentioned composite treatment.

[0025] From the viewpoint of ensuring sufficient adhesion to the current collector, the coverage rate of the resin on the surface of the active material particles is preferably 3% or more, more preferably 5% or more, and even more preferably 10% or more. The coverage rate of the resin on the surface of the carbon particles may be 60% or less, 50% or less, or 40% or less.

[0026] The coverage rate of the carbon particle surface with the resin was measured by an image analysis method. As an image analysis method, for example, a method of performing F mapping using energy dispersive X-ray spectroscopy (EDX) can be cited. Specifically, carbon particles coated with resin are observed using a scanning electron microscope (SEM), and F mapping is performed using EDX. Region X corresponding to the carbon particles and region Y where the resin (F) exists in region X are binarized, and the coverage is calculated according to the following formula. Coverage (%) = (area of ​​Y / area of ​​X) × 100

[0027] There is no particular limitation on the thickness of the first electrode formed in step 1. For example, the thickness of the first electrode can be selected from a range of 10 μm to 200 μm. The material of the current collector used in step 1 is not particularly limited, and can be selected from known materials such as aluminum, copper, nickel, titanium, and stainless steel. Process 2

[0028] In step 2, a second electrode layer is formed on the first electrode layer. The second electrode is formed by rolling film formation. The method of manufacturing the second electrode by calendaring film formation is the same as the method of manufacturing the above-mentioned first electrode by calendaring film formation. Unlike the first electrode layer, the second electrode layer is not in contact with the current collector. Therefore, unlike the case where the first electrode is produced by rolling film formation, at least a portion of the surface of the active material particles need not be coated with a resin other than PTFE.

[0029] The material used in the preparation of the second electrode is the same as the material used in the preparation of the first electrode described above. Among the materials for the second electrode layer, the amount of the binder relative to 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 to 10 parts by mass, or 1 to 5 parts by mass. Among the materials for the second electrode layer, the amount of the conductive material relative to 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 to 10 parts by mass or 1 to 5 parts by mass.

[0030] There is no particular limitation on the thickness of the second electrode produced in step 2. For example, the thickness of the second electrode can be selected from a range of 10 μm to 200 μm.

[0031] In the method disclosed herein, the method of integrating the electrode layer produced by calendering and the current collector is not particularly limited, and the method can be performed using a roll press, a flat plate press, or the like. When the first electrode layer is produced by electrostatic film formation or wet film formation, the current collector with the first electrode layer formed on the surface is integrated with the second electrode layer. When the first electrode layer is produced by rolling film formation, the current collector, the first electrode layer, and the second electrode layer are integrated. From the viewpoint of work efficiency, it is preferred that the current collector, the first electrode layer, and the second electrode layer are integrated at the same time. electrode

[0032] The electrode disclosed in the present invention includes a current collector, a first electrode layer disposed on the current collector, and a second electrode layer disposed on the first electrode layer. The first electrode layer includes active material particles and a resin in which the ratio of PTFE is 0 mass % or more and less than 5 mass %, or active material particles at least part of the surface of which is coated with a resin different from PTFE, and fibrous PTFE. The second electrode layer contains active material particles and fibrous PTFE.

[0033] In the electrode of the present disclosure, the current collector is not in contact with the second electrode including active material particles and fibrous PTFE, and the first electrode layer is disposed between the current collector and the second electrode. The first electrode layer comprises active material particles, and a resin having a PTFE ratio of 0 mass % or more and less than 5 mass %, or comprises active material particles at least a portion of the surface of which is coated with a resin different from PTFE, and fibrous PTFE. Thus, the first electrode layer exhibits sufficient adhesion to the current collector. Therefore, the electrode of the present disclosure has sufficiently low interface resistance at the interface between the current collector and the electrode layer, and exhibits excellent electron conductivity.

[0034] The details and preferred aspects of the electrode and each material contained in the electrode of the present disclosure are the same as the details and preferred aspects of the electrode produced by the above-mentioned method for producing an electrode and each material used therein.

[0035] In the first electrode layer, the amount of the resin relative to 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 parts by mass to 10 parts by mass, or 1 part by mass to 5 parts by mass. When the first electrode layer contains a conductive material, the amount of the conductive material relative to 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 to 10 parts by mass or 1 to 5 parts by mass.

[0036] In the second electrode layer, the amount of PTFE per 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 to 10 parts by mass or 1 to 5 parts by mass. When the second electrode layer contains a conductive material, the amount of the conductive material relative to 100 parts by mass of the active material particles can be selected from the range of, for example, 0.1 to 10 parts by mass or 1 to 5 parts by mass. Battery

[0037] The battery of the present disclosure includes the electrode of the present disclosure described above. The battery disclosed herein includes the electrode disclosed herein as at least one of a positive electrode and a negative electrode. In one embodiment, the battery disclosed herein includes the electrode disclosed herein as a positive electrode.

[0038] The type of battery disclosed in the present invention is not particularly limited and can be selected from lithium-ion secondary batteries (including liquid batteries and all-solid-state batteries), lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, cobalt-titanium-lithium secondary batteries, sodium-ion secondary batteries and the like.

[0039] Hereinafter, the present disclosure will be described in further detail using examples, but the present invention is not limited to these examples. Example 1

[0040] The following materials were put into MP mixer (COKE & ENGINEERING, Japan) and composited at 10000 rpm for 10 minutes. SEM observation of active material particles after composite treatment showed that the conductive material was fixed on the surface and the surface was covered with PVdF. Active material particles: NCM (volume average particle size: 10 μm, 96.6 parts by mass) Conductive material: acetylene black (1.5 parts by mass) Binder: PVdF (1.6 parts by mass)

[0041] Using an electrostatic screen film forming apparatus (Belku Industries), a layer containing active material particles after the composite treatment was formed on an aluminum foil (thickness: 12 μm) as a current collector to obtain a laminate. The film forming conditions were 1.5 kV, and the distance between the current collector and the screen was 1 cm. A load of 5 tons was applied to the laminate for 1 minute using two flat plates heated to 180° C. This softened or melted the binder in the layer containing the active material particles, fixed the active material particles to the current collector, and formed the first electrode layer on the current collector.

[0042] The following materials were put into MP mixer (COKE & ENGINEERING, Japan) and mixed at 300 rpm for 180 seconds. Next, further mixed at 5000 rpm for 500 seconds to form a granulated body in which a part of the PTFE particles was fibrillated and the active material particles were bonded together by the fibrillated PTFE. Active material particles: NCM (volume average particle size: 10 μm, 96.5 parts by mass) Conductive material: acetylene black (1.5 parts by mass) Binder: PTFE (2.0 parts by mass)

[0043] The mixture including the granules was rolled using a roll press (linear pressure: 0.4 t / cm) to fiberize the PTFE and form it into a sheet (thickness: 120 μm), thereby producing a second electrode layer as an independent film. The obtained second electrode layer was bonded to the surface of the aluminum foil on which the first electrode layer was formed using a roll press (linear pressure: 0.4 t / cm, 160° C.).

[0044] Through the above steps, an electrode is obtained in which the first electrode layer produced by electrostatic film formation and the second electrode layer produced by rolling film formation are arranged on the current collector. Example 2

[0045] The following materials were put into an MP mixer (COKE & ENGINEERING, Japan) and subjected to a composite treatment at 10,000 rpm for 10 minutes. The amounts of PVdF and PTFE were set so that the total volume was equal to the total volume of the binder used in Example 1. Active material particles: NCM (volume average particle size: 10 μm, 96.6 parts by mass) Conductive material: acetylene black (1.5 parts by mass) Binder: PVdF (0.5 parts by mass)

[0046] PTFE (1.4 parts by mass) was further added to the MP mixer after the composite treatment, and mixed at 300 rpm for 180 seconds. Next, the mixture was further mixed at 5000 rpm for 500 seconds to form a granulated body in which the active material particles were bonded together by the fibrillated PTFE.

[0047] The mixture including the granules was rolled using a roll press (linear pressure: 0.4 t / cm) to fiberize the PTFE and form it into a sheet (thickness: 120 μm), thereby producing a first electrode layer as an independent film. An aluminum foil (thickness: 12 μm) as a current collector, a first electrode layer, and a second electrode layer produced in the same manner as the second electrode layer of Example 1 were laminated together using a roll press (linear pressure: 0.4 t / cm, 160° C.).

[0048] Through the above steps, a positive electrode is obtained in which the first electrode layer produced by electrostatic film formation and the second electrode layer produced by rolling film formation are arranged on the current collector. Comparative Example 1

[0049] Aluminum foil (thickness: 12 μm) as a current collector, a first electrode layer produced in the same manner as the second electrode layer of Example 1, and a second electrode layer produced in the same manner as the second electrode layer of Example 1 were laminated together using a roll press (linear pressure: 0.4 t / cm, 160° C.).

[0050] Through the above steps, a positive electrode is obtained in which the first electrode layer produced by rolling film formation and the second electrode layer produced by rolling film formation are arranged on the current collector. Evaluation of electronic conductivity

[0051] As an index of the electronic conductivity of the electrodes produced in Examples and Comparative Examples, the resistance at the interface between the first electrode layer and the current collector (interface resistance) was measured using an electrode resistance measurement system RM2610 (Hioki Electric Co., Ltd., Japan). Table 1 First electrode layer Second electrode layer <![CDATA[Interface resistance [Ω·cm 2 > Comparative Example 1 Calendering film (without PVdF coating) Calendering film 1.0 Example 1 Electrostatic film forming Calendering film 0.5 Example 2 Calendering film (with PVdF coating) Calendering film 0.8

[0052] As shown in Table 1, for the positive electrode of (i) Example 1 in which the first electrode layer is produced by electrostatic film formation, and (ii) Example 2 in which the first electrode layer is produced by calendaring film formation and the active material particles contained in the first electrode layer are coated with PVdF, the interface resistance at the interface between the first electrode layer and the current collector is lower than that of the positive electrode of Comparative Example 1. In the positive electrode of Comparative Example 1, the first electrode layer is produced by calendaring film formation, and the active material particles contained in the first electrode layer are not coated with PVdF. The above results are considered to be because the first electrodes produced in Examples 1 and 2 have better adhesion to the current collector than the first electrode produced in Comparative Example 1.

Claims

1. A method for manufacturing an electrode, comprising: A step of manufacturing a first electrode layer disposed on the current collector; and a step of manufacturing a second electrode layer disposed on the first electrode layer, The first electrode layer is produced by electrostatic film forming, wet film forming, or calendering film forming. The second electrode layer is produced by calendering film formation. When the first electrode layer is produced by calendaring film formation, at least a part of the surface of the active material particles used in the calendaring film formation is coated with a resin different from polytetrafluoroethylene.

2. The method for manufacturing an electrode according to claim 1, wherein: The calendering film formation includes fiberizing polytetrafluoroethylene in a mixture containing active material particles and polytetrafluoroethylene.

3. The method for manufacturing an electrode according to claim 1, wherein: The resin different from polytetrafluoroethylene is polyvinylidene fluoride.

4. An electrode, The device comprises a current collector, a first electrode layer disposed on the current collector, and a second electrode layer disposed on the first electrode layer. The first electrode layer comprises active material particles and a resin having a polytetrafluoroethylene ratio of 0 mass % or more and less than 5 mass %, or comprises active material particles at least a portion of the surface of which is coated with a resin different from PTFE, and fibrous PTFE, The second electrode layer contains active material particles and fibrous PTFE.

5. A battery, It comprises the electrode according to claim 4.

Citation Information

Patent Citations

  • Electrode film for energy storage device, electrode and energy storage device

    JP2022003694A